A reta de Euler e a circunferência dos nove pontos: um olhar algébrico - Souto, Antonio Marcos da Silva (2013)
This work is the result of a research on the Euler line and the circumference of the nine points. The software geogebra was used to illustrate geometric constructions and present some practical activities for the study of notable points of the triangle, the Euler line and the circumference of the nine points to high school students. However, the work was based on the proof, with the use of Modern Algebra and Linear Algebra, the existence and properties of the object of this research, especially the universal property of points in the plane, critical in these demonstrations.